ADVANCE CARE DIRECTIVES (ACDS): CONSISTENCY AND UNDERSTANDING OF PATIENTS' FUTURE MEDICAL TREATMENT PREFERENCES. Issue 2 (1st June 2013) - Wallis, K; Sellars, M; Detering, K; Whiteside, K; Mawren, D; Silvester, W
Abstract : Background: ACDs enable individuals to document future treatment preferences. Documented wishes need to be 'clinically meaningful' and able to inform medical treatment plans during acute hospitalisation. Aim: To assess preferences indicated on ACDs for content, consistency within the document and concordance with medical orders on the Resuscitation Plan (RP) (hospital POLST form). Methods: Retrospective analysis of ACDs completed during facilitated advance care planning in 2011; including assessing consistency between the specific treatment wishes (CPR/Life-Prolonging Treatment (LPT)) and documented outcome preferences, and evaluating concordance of RP orders and ACD requests. Results: 153 patients completed ACDs, 88% also appointed a Substitute-Decision-Maker and 90% documented CPR/LPT preferences. Of these 51% chose 'No CPR', 40% chose 'CPR if medically beneficial' and 9% accepted medical advice that 'CPR would be of no benefit'. 48% indicated they didn't want LPT, 50% wanted LPT if doctors anticipated a reasonable outcome and only 2% wanted LPT for as long as possible. 71% identified other undesired treatment(s) (38% ventilation, 37% artificial nutrition, 12% surgery, 10% dialysis). 84% documented their interpretation of unacceptable outcomes (inability to eat—38%, or communicate—43%, impaired cognition 33%, bedbound 33%).CPR and LPT requests were internally consistent in 88% and 85% of cases. A RP was completed during admission in 70 patients; 89% were concordant with ACD requests, 10% limited treatment more and 1% recommended more treatment. Discussion: Most patients clearly documented preferences and undesired outcomes that were interpretable into actionable medical orders which were followed. Conclusion: Facilitated ACD completion ensures patients' wishes are known and respected.